Character, Incidence, and Predictors of Knee Pain and Activity After Infrapatellar Intramedullary Nailing of an Isolated Tibia Fracture. Issue 3 (March 2016) - Obremskey, William; Agel, Julie; Archer, Kristin; To, Philip; Tornetta, Paul
Abstract : Objective: To study the activity and incidence of knee pain after sustaining an isolated tibia fracture treated with an infrapatellar intramedullary nail at 1 year. Design: Retrospective review of prospective cohort. Setting: Multicenter Academic and Community hospitals. Patients: Four hundred thirty-seven patients with an isolated tibia fracture completed a 12-month assessment on pain and self-reported activity. Intervention: Infrapatellar intramedullary nail. Outcomes: Demographic information, comorbid conditions, injury characteristics, and surgical technique were recorded. Knee pain was defined on a 1–7 scale with 1 being "no pain" and 7 being a "very great deal of pain." Knee pain >4 was considered clinically significant. Patients reported if they were "able, " "able with difficulty, " or "unable" to perform the following activities: kneel, run, climb stairs, and walk prolonged. Variables were tested in multilevel multivariable regression analyses. Results: In knee pain, 11% of patients reported a "good deal" to a "very great deal" of pain (>4), and 52% of patients reported "no" or "very little" pain at 12 months. In activity at 12 months, 26% and 29% of patients were unable to kneel or run, respectively, and 31% and 35% of patients, respectively, stated they were able with difficulty or unable to use stairs or walk. Conclusions: Clinically significant knee pain (>4/7) was present in 11% of patients 1 year after a tibia fracture. Of note, 31%–71% of patients had difficulty performing or were unable to perform routine daily activities of kneeling, running, and stair climbing, or walking prolonged distances. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.